Analisis Penerapan Pembiayaan Murabahah Berdasarkan Pesanan dan Tanpa Pesanan serta Kesesuaian dengan PSAK 102 - Muhammad Yusuf (Binus Business Review, 2013)
The development of banking industries in Indonesia is followed by many Islamic banks popping up that offer different products with existing products in the conventional banking products: murabahah which is the flagship product of Islamic banks so that the proportion is the most dominating product among other products. Murabahah is a sale and purchase agreement with the selling price of goods at cost plus an agreed profit which the seller must disclose the cost of the goods to the buyer. This study aims to investigate the implementation of Murabahah financing at Syariat Bank X and to know the accounting treatment of murabahah in Syariat Bank X and compliance with PSAK 102. The research problem is how the application and the accounting treatment of Murabahah in Bank Syariat X year 2010 - 2011 and compliance with PSAK 102. This study used qualitative approach to the secondary data collection methods and interviews with Syariat Bank X management. The results of the study showed that in terms of the accounting treatment of Murabahah transactions, the accounting treatment of Murabahah in Syariat Bank X is not in accordance with PSAK 102 on Accounting for Murabahah Syariat Bank X  in implementing orders only apply where an order only, whereas PSAK 102, murabahah can be done with/without any order. And in the case of disclosure of accounting murabahah, there is a lack of Syariat Bank X from the seller or the bank without the express terms of the purchaser. Based on this research, Syariat Bank X should complete in terms of disclosure of accounting disclosure Murabahah which explains in terms of the buyer and implementing murabahah without orders in accordance with PSAK 102.